Guardians of the boardroom: the protective power of the business judgment rule in Malaysia - Sharija Che ShaariI; Junaidah Zeno; Ida Shafinaz Mohamed Kamil (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2024)
The Business Judgment Rule (BJR) protects directors from liability when they make business decisions in good faith and with due care. Granting directors a legal shield is important to encourage bold strategic decision-making without fear of constant litigation. This paper examines the extent to which the BJR protects Malaysian directors from personal liability when making business decisions by analysing the Companies Act 2016 and relevant case law through a doctrinal methodology. It is found that the BJR is not a blanket immunity for the directors as they are accountable for decisions made with fraud, conflicts of interest, or gross negligence. Hence, the BJR strikes a balance between protecting directors from frivolous lawsuits and holding them accountable for negligent or fraudulent behaviour. This paper concludes that the BJR is important in encouraging bold strategic decision-making while ensuring director accountability. This paper contributes to the existing literature by analysing the specific application of the BJR in the context of the Malaysian Companies Act 2016.